Confirmation and follow up of initial "NAT yields": Prospective study from a tertiary healthcare center in India. Issue 2 (April 2016) - Pandey, Prashant; Tiwari, Aseem Kumar; Dara, Ravi C.; Rawat, Ganesh Singh; Negi, Avinash; Raina, Vimarsh
Abstract: Background: In India variable rate of "NAT yield" has been demonstrated in several published reports. This study was performed with the objective to know the rate of "true NAT yield" in blood donors by confirmation with supplementary tests and follow up of initial "NAT yield" donors. Materials and Methods: A total of 48, 441 blood donors were tested for HIV, HBV and HCV with enhanced chemiluminescence and ID-NAT. To know the true NAT yield status confirmation of NAT yield donors was done as with an array of serological tests, repeat ID-NAT and alternate NAT. Results: The cumulative initial "NAT yield" rate was 1:4404 (11/48, 441). Seven of 11 initial "NAT yields" were for hepatitis B whereas two each were in HIV and HCV. Among the 11 "NAT-yield" donors, eight donors were followed-up for confirmation. Out of these eight donors only 4 were found to be true HBV NAT yields. Out of four true NAT yields two were window period donations while the other two were occult hepatitis B infection with anti-HBcore total positive. Conclusion: Our findings suggest that all "initial NAT yields" may not be "true NAT yields". We would also like to suggest that to demonstrate the true "NAT yield" status supplementary tests and donor follow up are important to differentiate true NAT yields.